Nilai dan Peranan Sosial Perempuan Bali Di Kota Baubau - Rosmawati Rosmawati (Universitas Muhammadiyah Makassar, 2017)
Each family member has a role in a family unit, including wives who have a central role in domestic territory but also sometimes work in the public domain. Technique of data collection is done by using observation, interview, and documentation. Data analysis technique used in this research is using qualitative descriptive analysis. The results showed that culture and belief in religious teachings is one of the factors behind the formation of work ethic of Balinese women in living their lives. Activity work is based on the belief in Karmapala's law which is believed to be a form of karma from the results of good and bad deeds that bring a high adherence attitude to the planting of virtue values in every act that is born through sincere devotion and sacrifice. To that end, Balinese women always attach great importance to good relations in their every action, hard work, willing to work hard, to sacrifice to slave workers only to achieve a better life later through the process of rebirth (Rengkarnasi) as a measure of deeds of every deed.Keywords: Value, Role, Bali Women